2006
DOI: 10.1080/13697130600861542
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal symptoms and health problems of women aged 50–65 years in Southern Jordan

Abstract: Women in southern Jordan experienced multiple menopause-related symptoms and morbidities. The majority of them did not receive any health education about this phase of life. Preventive health practices and health-promoting behaviors are relatively uncommon. Effective health-care delivery systems responsive to menopausal women's health needs are highly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
0
10
0
3
Order By: Relevance
“…The most frequently reported somatic symptoms among Jordanian menopausal women are joint aches, bone pains, hot flushes and urinary incontinence. Additional symptoms include irritability and mood changes, weight gain and headaches 10 .…”
Section: Severity Of Menopausal Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently reported somatic symptoms among Jordanian menopausal women are joint aches, bone pains, hot flushes and urinary incontinence. Additional symptoms include irritability and mood changes, weight gain and headaches 10 .…”
Section: Severity Of Menopausal Symptomsmentioning
confidence: 99%
“…Al-Qutob 13 reported that Jordanian menopausal women complained of an appreciable level of morbidity including 'urinary incontinence', 'urinary tract infections', 'reproductive tract infections' and 'genital prolapse' 13 . Jordanian menopausal women complained mostly of somatic symptoms including joint aches and bone pain, hot flushes, and irritability and mood changes 10 . In a recent qualitative study by Mahadeen and colleagues 28 , Jordanian women considered menopause as a life transition, with no reproduction, leading to a stage of freedom, relief and rest.…”
Section: Factors Affecting the Severity Of Menopausal Symptomsmentioning
confidence: 99%
“…This includes a median age of 50 reported in a study including 858 Saudi Arabian women of which 391 were postmenopausal [ 54 ], a median age of natural menopause of 49.3 years for 298 women in Lebanon [ 55 ], and a median age of 50 based on a study of 143 women in Jordan [ 56 ]. The mean age recalled by a sample of 1, 397 women in Iran was 47.7 ± 4.9 years [ 57 ].…”
Section: Middle Eastmentioning
confidence: 98%
“…• Menopause: One of the most common reported somatic symptoms is paresthesia in the extremities (102). Decreasing estrogen production causes decreased structural effectiveness of collagen and thinning of the skin.…”
Section: Metabolic Disordersmentioning
confidence: 99%